Numerical analysis of composite concrete and steel slabs section under fire situation - Barcellos, Francine; Bolina, Fabrício; Tutikian, Bernardo (Revista ALCONPAT, 2019)
This work aims to evaluate the performance of composite slabs under fire, correlating them to the project at normal temperature, according to NBR 14323 (ABNT, 2013), NBR 8800 (ABNT, 2008) and NBR 14762 (ABNT, 2010). ), through the heating curve of ISO 834 (ISO, 1999) and distribution of slab temperatures obtained by using Ansys software. The computational models were calibrated according to the standard and extrapolated to other design scenarios, with different geometries, thicknesses and effective thicknesses of the concrete layer. As results, the steel deck with recesses had better performance in relation to the trapezoids, being the thickness of the concrete layer the preponderant variable in the behavior of these slabs at high temperatures, due to their greater thermal stability.